2018
DOI: 10.12688/f1000research.14499.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in prostate cancer research: large-scale genomic analyses reveal novel driver mutations and DNA repair defects

Abstract: Prostate cancer (PCa) is a disease of mutated and misregulated genes. However, primary prostate tumors have relatively few mutations, and only three genes ( ERG, PTEN, and SPOP) are recurrently mutated in more than 10% of primary tumors. On the other hand, metastatic castration-resistant tumors have more mutations, but, with the exception of the androgen receptor gene ( AR), no single gene is altered in more than half of tumors. Structural genomic rearrangements are common, including ERG fusions, copy gains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 212 publications
(331 reference statements)
0
43
0
Order By: Relevance
“…TMPRSS2 has a role in the entry of several coronaviruses, including SARS-CoV2, SARS-CoV, and MERS-CoV, as well as several types of influenza viruses (2,(8)(9)(10)(11)(12). TMPRSS2 also functions as an oncogene in prostate cancer, in which fusion events of TMPRSS2 and ERG2 occur (13). Therefore, TMPRSS2 is a promising target for drug development.…”
Section: Discussionmentioning
confidence: 99%
“…TMPRSS2 has a role in the entry of several coronaviruses, including SARS-CoV2, SARS-CoV, and MERS-CoV, as well as several types of influenza viruses (2,(8)(9)(10)(11)(12). TMPRSS2 also functions as an oncogene in prostate cancer, in which fusion events of TMPRSS2 and ERG2 occur (13). Therefore, TMPRSS2 is a promising target for drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on comprehensive characterization of the prostate cancer transcriptome and genome have revealed that p53 gene represents one of the most frequently mutated driver gene in primary prostate cancer [51] and mutations in p53 gene also occur at remarkably high frequency in metastatic tumors and metastatic castrationresistant prostate cancer (mCRPC) [52][53][54]. Mutations in the p53 gene occur at different stages of prostate tumorigenesis from early stage prostate cancer to its invasive or metastatic tumors or mCRPC, suggesting that p53 mutant is a potential target for therapeutic interventions in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Correlates of Oncogenic Signaling. Genomic studies of prostate cancer have identified driver alterations associated with disease progression (39). We sought to define how the variable cassette exons we identified and the biological processes they participate in might relate to these oncogenic signals.…”
Section: Combining Gene Pathway Analysis and Exon Usage Identifies Exonmentioning
confidence: 99%